Reading Strategies Used by Higher Education Students in the TOEFL Reading Comprehension Section - Wicaksono, Agung; Suhartono, Suhartono; Jatmiko, Jatmiko (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
This study investigates the reading strategies employed by 32 higher education students while completing the TOEFL Reading Comprehension section. The participants were categorized into three performance groups: excellent (10%), fair (50%), and poor (40%). Using a mixed-methods approach, this research examines the strategies most commonly used, their correlation with test scores, and provides recommendations for improving reading comprehension skills. The findings highlight that effective strategies such as contextual guessing, scanning, and skimming were commonly used, while time management and in-depth analysis were essential for differentiating high performers from low performers. Students with higher scores prioritized time management, paraphrasing, and skimming to grasp the structure before deep reading, while students with lower scores often resorted to word-for-word translation, leading to inefficiency. These results emphasize the importance of strategic reading in TOEFL performance. The study suggests that programs focused on enhancing reading strategies could significantly improve TOEFL reading scores. This study contributes to the understanding of how strategic reading can influence the success of non-native English speakers in standardized tests. Further research is needed to explore more targeted interventions for improving reading strategies among diverse student groups.